Peran Aktor Kebijakan Dalam Pelaksanaan Pengadaan Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) Guru di Ruang Lingkup Pemerintah Provinsi Riau : (Studi Kasus Kota Pekanbaru) (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The policy on the procurement of Government Employees with Work Agreements (PPPK) for teachers is a program aimed at providing employment status certainty for honorary teachers and improving the quality of education personnel. In Riau Province, particularly in Pekanbaru City, this policy still faces problems, such as the placement of teachers not matching their original teaching schools and many teachers who have passed the passing grade yet have not received placement. This study analyzes the role of policy actors in the implementation of the PPPK Teacher program and the challenges encountered. The method used is qualitative descriptive with a case study approach, through interviews, observation, and documentation. The theory applied is the policy actor role theory by Anderson (Yuliani & Abdul, 2022), which consists of four indicators: participation, perspective, accessibility, and decision-making. The results indicate that the National Civil Service Agency (BKN) Regional XII Pekanbaru, the Riau Provincial Civil Service Agency (BKD), and the Riau Provincial Education Office have effectively performed their roles as policy actors; however, challenges remain regarding the limited authority of regional agencies, the mismatch between the number of allocated positions and actual needs, and requests for reassignment.